The role of human β-defensin 2 (HbD-2) and cathelicidin (LL-37) in the local protection of the upper respiratory tract in children with allergic rhinitis and bronchial asthma - Yu.K. Bolbot; T.A. Bordiі; Ya.V. Vilenskyi (Medičnì Perspektivi)
Allergic diseases of the respiratory system seriously affect the psychological, physical and social aspects of the live of sick children, morally and financially exhausting members of their families as well. It is known that exacerbations of allergic diseases of the respiratory tract occur due to interaction with numerous triggers, one of which is a respiratory viral infection. At the same time, it is widely known that patients with allergic respiratory diseases are more prone to to acute respiratory infections. One of the reasons for this tendency often is an insufficient activity of non-specific factors of local immunity of the respiratory system – endogenous amphiphilic antimicrobial peptides, in particular the most studied their representatives - the family of defensins and human cathelicidin. Current research proves that these antimicrobial peptides are characterized by broad antiviral, antimicrobial and immunomodulatory activity. The aim of this study was to study the concentrations of local immune factors - human HbD-2 and LL-37 - in the secretion of the mucous membranes of the upper respiratory tract in children with asthma and allergic rhinitis and to clarify their role in protection against respiratory viral infections in this contingent of patients. We performed laboratory and clinical examinations of 76 children aged 7 to 18 years, of whom 24 were diagnosed with allergic rhinitis, 28 children - bronchial asthma, and 24 - bronchial asthma and allergic rhinitis. The control group consisted of 20 healthy children of the appropriate sex and age. In addition to general clinical methods, patterns of respiratory morbidity were analyzed and concentrations of antimicrobial peptides were determined: by ELISA human cathelicidin (LL-37), β-defensin 2 (HbD-2) in the secretion of the upper respiratory tract, statistical analysis was performed. It was found that children with allergic diseases of the respiratory tract are characterized by a higher frequency of acute respiratory infections with more frequent involvement of the lower respiratory tract, which led to an increase in the duration of the disease compared to their healthy peers. In children with allergic rhinitis and bronchial asthma, there was revealed a significant decrease in the concentrations of antimicrobial peptides in the secretion of the upper respiratory tract compared with the control group.